Theology and psychology – the interdisciplinary work of Fraser Watts - Smith, Willem J. (HTS teologiese studies, 2005)
In the preface to his book, Theology and Psychology, Fraser Watts, a lecturer in Theology and Natural Science at the University of Cambridge, states that he approaches “… the interface between theology and psychology by looking at each discipline from the perspective of the other. This includes a religious perspective on several current hot topics in psychology, such as evolution, neuroscience, and computer intelligence. I also consider theological topics like divine action, salvation history and eschatology, in each case using the psychological perspective in a different way”. By taking an interdisciplinary approach, Watts aims at proposing a psychology of religious experience. He considers theology to be the rational reflection on the Christian tradition. When exponents of this tradition are in dialogue with exponents of psychology, the focus falls on human nature. Watts admits that a certain lack of competence in one of the two disciplines can be a problem when working in an interdisciplinary way. However, he is willing to take the risk. Watts worked in psychology for 25 years and was also involved with a medical research council, before taking up a position at the Faculty of Divinity, University of Cambridge.